Aulus Cornelius Celsus – a famous Roman encyclopedist - Supady, Jerzy (Health Promotion & Physical Activity, 2020)
The ancient Romans did not work as physicians, but they used the services of foreign doctors, mostly Greeks. During the times of the Roman Empire there emerged a class of well-educated patricians, who possessed knowledge in various field. Aulus Cornelius Celsus, the author of a voluminous work, was one of such patricians. Of the numerous volumes of his encyclopaedia only a fragment on medicine in extant. The piece which remains intact is a collection of medical knowledge of those times.